Analysis of PSPHL as a Candidate Gene Influencing the Racial Disparity in Endometrial Cancer - Allard, Jay; Chandramouli, Gadisetti; Stagliano, Katherine; Hood, Brian; Litzi, Tracy; Shoji, Yutaka; Boyd, Jeff; Berchuck, Andrew; Conrads, Thomas; Maxwell, Larry; Risinger, John (Frontiers in Oncology, 2012)
Endometrial cancer is the most commonly diagnosed gynecologic malignancy in the United States and is characterized by a well recognized racial disparity in both incidence and survival. Specifically Caucasians are about two times more likely to develop endometrial cancer than are African Americans. However, African American women are more likely to die from this disease than are Caucasians. The basis for this disparity remains unknown. Previous studies have identified differences in the types and frequencies of gene mutations among endometrial cancers from Caucasians and African Americans suggesting. We performed a gene expression microarray study in an effort to further examine differences between African American and Caucasian women’s endometrial cancers. This expression screen identified a list of potential biomarkers differentially expressed between these two groups of cancers. Of these we identified a poorly characterized transcript with a region of homology to phospho serine phospatase (PSPH) and designated phospho serine phospatase like (PSPHL) as the most differentially over-expressed gene in cancers from African Americans. We clarified the nature of expressed transcripts. Northern blot analysis confirmed PSPHL messages under 1 KB. Sequence analysis of transcripts confirmed two alternate open reading frame (ORF) isoforms due to alternative splicing events. Splice specific primer sets confirmed both isoforms were differentially expressed in tissues from Caucasians and African Americans. We further examined the expression in other tissues from women to include normal endometrium, normal and malignant ovary. In all cases PSPHL expression was more often present in tissues from African-Americans than Caucasians. Our data confirm the African-American based expression of the PSPHL transcript several tissue types. PSPHL represents a candidate gene that might influence the observed racial disparity in endometrial and other cancers.